Influence of LLDPE-g-MA on Mechanical Properties, Degradation Performance and Water Absorption of Thermoplastic Sago Starch Blends - Denny Akbar Tanjung; Novesar Jamarun; Syukri Arief; Hermansyah Aziz; Ahmad Hafizullah Ritonga; Boy isfa (Universitas Gadjah Mada, 2022)
The addition of LLDPE-g-MA into the compound of sago starch/LLDPE was studied to improve its mechanical, morphology, degradation performance, and water absorption properties. Thermoplastic Sago Starch was composed of a mixture of sago starch and glycerol. LLDPE-g-MA was prepared in varied concentrations based on the weight of TPSS (0, 6, 8, 10, and 14 wt.%) by reacting LLDPE, maleic anhydride, and benzoyl peroxide using an internal mixer. The results showed an increase in values obtained from mechanical tests, i.e., tensile strength was improved from 0.6902 to 3.6187 N/mm2 with the addition of LLDPE-g-MA at 10 wt.%. The addition also resulted in a 1.44% increment in elongation at break and 251 N/mm2 for Young's Modulus. The surface morphology of the sample demonstrated an excellent interfacial adhesion reaction or LLDPE dispersion over the entire surface of the matrix (starch). The water absorption test continued to decrease with the increase in the LLDPE-g-MA concentration from 53 wt.% (without LLDPE-g-MA) to 14 wt.% at 10 wt.% LLDPE-g-MA concentration. The degradation performance showed that the sample could be degraded under all three conditions for up to 30 days.